-12=-7k-5k

Simple and best practice solution for -12=-7k-5k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=-7k-5k equation:


Simplifying
-12 = -7k + -5k

Combine like terms: -7k + -5k = -12k
-12 = -12k

Solving
-12 = -12k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '12k' to each side of the equation.
-12 + 12k = -12k + 12k

Combine like terms: -12k + 12k = 0
-12 + 12k = 0

Add '12' to each side of the equation.
-12 + 12 + 12k = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 12k = 0 + 12
12k = 0 + 12

Combine like terms: 0 + 12 = 12
12k = 12

Divide each side by '12'.
k = 1

Simplifying
k = 1

See similar equations:

| 2-x=30/(x-1) | | 15t^2-22tv-5v^2=0 | | 2x/5+8=13/5 | | x-(10/(x-1))=4 | | -3x^2+4=4x | | -7n-n=-24 | | x+x=30-10 | | 5+3q-4=2q+1 | | x-10/(x-1)=0 | | (t-7)(t-7)=(t+7)(t+7)+168 | | x-(10/(x-1))=0 | | 4+6(6x-1)=-5(-x+5)-8 | | 9x-12-2x=11x+6 | | 11-9x-7-6x=7 | | (x-2)+2(x-2)-24=0 | | -2p-6p=-24 | | 7=8x-4 | | (4x^2+16x+16)(x-2)=x^2-4 | | 2x^4-7x^2+2=0 | | 2t-3=3(t-4) | | 2-0.6k=2 | | 36=3(4-x) | | 5x+x=8x+55+9x | | 25x-3=35x+5 | | 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 | | 3x+27=20x-43 | | x/9+4=13 | | -9(x-4)+5x=-4(x+8)+5 | | 9*19+9= | | 2(4x+9)=-42+36 |

Equations solver categories